Method of Thermal Processing of Biomass With Heliopyrolysis Device - Davlonov Xayrulla Allamuratovich; Almardanov Hamidulla Abdiganiyevich; Toshboyev Abdumalik Rashid ugli; Umirov Fayzullo Baxodirovich (International Journal on Human-Computing Studies, 2021)
The article discusses the issues of ensuring the temperature regime in the reactor of the pyrolysis plant and the saving of thermal energy for private needs, as well as the analysis of the thermal performance of the plant. As a result of applying a solar concentrator to this type of pyrolysis device, a temperature of 300-500 ℃ can be obtained. This allows to reduce the private energy consumption for the pyrolysis process by up to 30%.